ANTIBODIES RESPONSE OF BROILERS TO LOCALLY PREPARED OIL BASED MYCOPLASMA GALLISEPTICUM VACCINE - M. A. Gondal; M. Rabbani; K. Muhammad; T. Yaqub; M. E. Babar; A. A. Sheikh; A. Ahmad; M. Z. Shabbir; M. I. Khan (Journal of Animal and Plant Sciences, 2013)
In the present study formaldehyde inactivated Montanide ISA70 based MG vaccine from the PCR confirmed positive local isolate was prepared and evaluated in broilers. An amount of immune gen per 0.3ml of the dose was 107 Colony forming units of the bacteria. At the age of 14 days, the broilers were randomly divided into three groups (A, B and C), each having twenty birds. Each bird of group A, B and C was inoculated with 0.3 ml of sterile Frey’s broth (negative control), indigenous vaccine (IN-VAC) and imported (IM-VAC; VaxFact-USA) subcutaneously at mid neck region, respectively. The birds of group A (Control group) showed 28.78± 2.53, 21.50± 2.23,14.55± 1.17, 7.18± 0.64, 4.67± 0.37 mean anti-MG ELISA titer on 0, 15, 30, 45 and 60 days of age, respectively. However, the birds of group B showed 29.38± 2.82,153.26±8.00, 332.67± 9.05, 475.78± 27.69, 500.03± 25.38 serum mean anti-MG ELISA titer on 0, 15, 30, 45 and 60 days of age, respectively and the birds of group C showed 28.57±2.25,106.77± 7.11, 286.13± 10.04, 353.45± 10.13, 489.89± 18.76 serum mean anti-MG ELISA titer on 0, 15, 30, 45 and 60 days of age respectively. It is concluded that oil based MG vaccine induces protective level of anti-MG-ELISA antibodies in broilers that persist for more than 45 days post priming. The oil base vaccine did not interfere with the maternal antibody titer of the birds.
Keywords: Mycoplasma gallisepticum; CRD; Immunogen; Montanide ISA70; MG Bacterin